Glycemic and insulinemic responses to small repeated carbohydrate feedings before exercise - Short, K. R.; Sheffield-Moore, M.; Parcell, A. C.; Bolster, D. R.; Costill, D. L. (Medicine & Science in Sports & Exercise, 1997)
Whether consuming several small feedings, rather than the traditional single bolus, would alter blood glucose and insulin responses during rest and exercise was determined. Trained cyclists (N = 8) ingested either 22.5, 45, or 75 total grams of maltodextrin and dextrose dissolved in 473 ml of water or an equal volume of placebo. Four portions of drink were consumed at 15-min intervals in the hour before completing a 2-hour bike ride at 65-70% VO2max. Both single and multiple doses of CHO produced the same effects of hypoglycemia near the onset of exercise. The magnitude of the response appeared to be unrelated to the amount of CHO consumed. Implication. There is a critical amount of CHO that needs to be ingested to produce an hypoglycemic response. Increasing beyond that amount does not "improve" the response any further.